Determination of arsenic speciation and the possible source of methylated arsenic in Panax Notoginseng. (February 2017) - Zhu, Meilin; Zeng, Xiancai; Jiang, Yanxue; Fan, Xiaoting; Chao, Sihong; Cao, Hongbin; Zhang, Wensheng
Abstract: Arsenic species and a possible source of methylated arsenic in a Panax Notoginseng (PN) medicinal plant were explored to further understand the change of inorganic arsenic to the less toxic methylated form to minimize the health risks associated with its medicinal use. Arsenic speciation in PN from major planting areas was determined using high-performance liquid chromatography coupled with hydride generator-atomic fluorescence (HPLC-HG-AFS). Pot experiments were performed to explore the source of methylated arsenic in PN, and the arsenite methyltransferase (arsM) gene abundance was determined using quantitative reverse transcription PCR (q-RTPCR). Methylated arsenic (monomethylarsonic acid (MMA) + dimethylarsinic acid (DMA)) accounted for 43% ± 30% of the total arsenic in PN from planting areas, while the primary species in soil was As(V) (94% ± 0.12%). In the pot experiments, methylated arsenic accounted for 37%–49% of the total arsenic in PN, and As (V) was the primary species in soil (>98%). The four detected arsenic species in PN increased as the amount of As added to soil increased. The methylated arsenic contents in the PN root were significantly positively correlated with the ArsM gene abundance in soil, suggesting that methylated arsenic in PN is likely from the planting soil. Highlights: Arsenic species in PN and soil were investigated using field and pot experiments. Inorganic As and methylated As were present in considerable amounts in PN. As(V) was the major species in soil, although methylated As was detected. Methylated As level in PN is positively correlated with ArsM gene abundance in soil. The methylated arsenic in PN was most likely from the planting soil.